Circularly Polarized Luminescence from Bischromophoric Cyanostilbene‐Derived Homochiral Nanostructures in Solution. Issue 8 (19th May 2020) - Sarkar, Souvik; Narayan, Bhawani; George, Subi J.
Abstract: Herein, we present the self‐assembly and chiroptical properties of enantiomeric bischromophoric molecules consisting of trans ‐(1, 2)‐cyclohexanediamide as the chiral core and cyanostilbene derivative as the fluorescent chromophores. These enantiomers form diverse organic nanostructures, such as vesicles and two‐dimensional sheets, in non‐polar solvents, exhibiting circularly polarized luminescence (CPL) with a remarkable luminescence dissymmetry factor, |glum |, in solution. Detailed spectroscopic probing reveals the formation of supramolecular conglomerate assemblies from its racemic mixture of monomers due to the chirality mismatch of the core. Abstract : Circularly polarized luminescence (CPL)‐active self‐assembled bischromophoric cyanostilbenes with a remarkable luminescence dissymmetry factor (glum ) have been realized in the solution state. Control over morphology can be achieved by fine‐tuning the concentration of the solution. Strong homochiral recognition of trans ‐1, 2‐bis(amido)cyclohexane enables formation of organic conglomerates in the solution, thus resulting in tunable CPL in co‐assembled enantiomeric solution.